2012
DOI: 10.1007/s12529-012-9263-0
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Changes in Women at Genetic Risk of Breast Cancer: an Observational Study

Abstract: Scottish women at increased risk of breast cancer have scope for protective changes in lifestyle and support a risk-reduction trial. The needs of younger women and of those with daughters should be addressed in its design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Breast screening and symptomatic clinics present an opportunity for a "teachable moment" for preventative breast cancer advice, supporting prior research in this setting, for example (Anderson et al, 2014;Conway et al, 2016;Macleod & Anderson, 2018;McLeish et al, 2013). Nevertheless, the specific challenges in communicating information about alcohol as a modifiable risk factor will need to be considered when developing an alcohol-focused intervention for women attending breast clinics.…”
Section: Con Clus Ionmentioning
confidence: 72%
“…Breast screening and symptomatic clinics present an opportunity for a "teachable moment" for preventative breast cancer advice, supporting prior research in this setting, for example (Anderson et al, 2014;Conway et al, 2016;Macleod & Anderson, 2018;McLeish et al, 2013). Nevertheless, the specific challenges in communicating information about alcohol as a modifiable risk factor will need to be considered when developing an alcohol-focused intervention for women attending breast clinics.…”
Section: Con Clus Ionmentioning
confidence: 72%
“…A familial diagnosis of cancer or abnormal pathological test results are situational cues that heighten perceptions of vulnerability and increase motivation to change behaviors. [6][7][8] Cancer survivors, and those at high risk for cancer, are placed in a "teachable moment" for health behavior change. 9 To capitalize on these teachable moments for primary and sec-ondary prevention of cancer disease, interventions that change health behaviors are necessary.…”
mentioning
confidence: 99%
“…Previous research has suggested that perceived risk, engaging in healthy behaviors and beliefs about control are connected. For example, McLeish et al (2013) reported that women who had a close relative with a BRCA mutation (but did not themselves have the mutation), who perceived their own breast cancer risk to be high (> 50 %), reported significantly more changes in health behaviors following risk assessment than those with lower risk perceptions (irrespective of professionally estimated risk). In the current study we did not find a simple association between perceived risk and engaging in healthy behaviors although we do not have any measure of changes that may have occurred after risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Such brief interventions in other clinical settings are beginning to show promise (Petrie et al 2002;O'Carroll et al 2013;O'Carroll 2014), and a trial of this approach based in the genetics clinic setting may be warranted. Previous work by McLeish et al (2013) in women attending breast cancer family history clinics reported that most women were willing to adopt changes in lifestyle (e.g. more exercise, less alcohol), although the authors noted that younger women (<40 years) and those with daughters had made fewer spontaneous changes and that Bspecial attention^would have to paid to this subgroup Bif their good intentions are to be translated into action^.…”
Section: Discussionmentioning
confidence: 99%